2011
DOI: 10.1155/2011/693691
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Rearrangements in Post‐Chernobyl Papillary Thyroid Carcinomas: Evaluation by Spectral Karyotyping and Automated Interphase FISH

Abstract: Structural genomic rearrangements are frequent findings in human cancers. Therefore, papillary thyroid carcinomas (PTCs) were investigated for chromosomal aberrations and rearrangements of the RET proto-oncogene. For this purpose, primary cultures from 23 PTC have been established and metaphase preparations were analysed by spectral karyotyping (SKY). In addition, interphase cell preparations of the same cases were investigated by fluorescence in situ hybridisation (FISH) for the presence of RET/PTC rearrangem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…Interphase fluorescence in situ hybridization (FISH) is the gold standard method for detecting gene rearrangements in a single cell and is the most sensitive means for identifying and quantifying intratumoral genetic heterogeneity (Nakazawa et al 2009, Drieschner et al 2011, Hieber et al 2011. However, as FISH requires expert operators and is a time-consuming technology, it is rarely used, and no FISH-based studies on fine-needle aspiration (FNA) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Interphase fluorescence in situ hybridization (FISH) is the gold standard method for detecting gene rearrangements in a single cell and is the most sensitive means for identifying and quantifying intratumoral genetic heterogeneity (Nakazawa et al 2009, Drieschner et al 2011, Hieber et al 2011. However, as FISH requires expert operators and is a time-consuming technology, it is rarely used, and no FISH-based studies on fine-needle aspiration (FNA) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Chromosomal abnormalities in both normal and atypical epithelial cells exfoliated in sputum were presented confirming that cellular genetic abnormalities of 3p22.1 and 10q22.3 reflect a field cancerization effect within the bronchial cells of individuals at high risk for developing cancer (43). Hieber et al screened cell cultures from papillary thyroid carcinomas for the presence of rearranged in transformation (RET)/papillary thyroid carcinomas (PTC) rearrangement (107). High frequency of RET rearrangement was found in Ukrainian patients after the Chernobil accident and the aberration was present only in a subset of tumor cells indicating genetic heterogeneity.…”
Section: Wide Range Of Applicationsmentioning
confidence: 95%
“…However, this method provides important information on the percentage of cells harboring the RET rearrangement and on its clonal/non-clonal occurrence (21,22). More recently, automated interphase FISH was successfully applied to detect RET/PTC in PTC primary cultures, a method that, suitably modified for clinical practice, could allow the analysis of a larger number of cells per sample and overcome a possible bias of the operator (38).…”
Section: Methods Of Detection For Ret/ptc Rearrangementsmentioning
confidence: 99%